1980
DOI: 10.1007/bf01868828
|View full text |Cite
|
Sign up to set email alerts
|

Glycerol treatment in mammalian skeletal muscle

Abstract: (1) The effects of glycerol-treatment on the ultrastructure, tension, and electrical properties of rat sternomastoid muscle fibers are described. (2) The effect upon the ultrastructure of fibers differed from that previously reported for amphibian fibers, in that the sarcoplasmic reticulum, as well as the T-system, was disrupted. (3) Tension (tension (tetanus and K-contracture) was abolished when preparations were returned to normal Krebs after exposure to a glycerol-Krebs solution (exposure periods were 1 hr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

1987
1987
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 20 publications
5
21
1
Order By: Relevance
“…These pharmacological treatments also potentiate the observed increase in [Ca 2ϩ ] r in swine muscle fibers from both genotypes (data not shown), suggesting that plasma-membrane Ca ] r in both genotypes. Previous work has shown that glycerol treatment disrupts excitation-contraction coupling in skeletal muscle by disconnection of the transverse tubular system from the extracellular space (32,33). Here we show that detubulation of MHN and MHS swine fibers induces a small increase in [Ca 2ϩ ] r in both types of muscle fibers (16% MHN and 10% MHS, respectively).…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…These pharmacological treatments also potentiate the observed increase in [Ca 2ϩ ] r in swine muscle fibers from both genotypes (data not shown), suggesting that plasma-membrane Ca ] r in both genotypes. Previous work has shown that glycerol treatment disrupts excitation-contraction coupling in skeletal muscle by disconnection of the transverse tubular system from the extracellular space (32,33). Here we show that detubulation of MHN and MHS swine fibers induces a small increase in [Ca 2ϩ ] r in both types of muscle fibers (16% MHN and 10% MHS, respectively).…”
Section: Discussionsupporting
confidence: 55%
“…Glycerol Treatment-It is well established that glycerol treatment can be used to osmotically disrupt the transverse tubules in skeletal muscle (32,33). Briefly, intact MHN and MHS swine muscle fibers were incubated in 350 mM glycerol solution for 1 h, and then returned to normal swine physiologic solution (32).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the higher temperature, twitch and tetanic tension were reduced 90° and 86 from control values of 43.0 ± 1.8 (n = 3) and 232.7 + 9.6 mN (n =3) respectively. DAVEY et al (1980) found that glycerol treatment abolished twitches and potassium contractures in a fast-twitch skeletal muscle. Experiments were carried out on four extensor digitorum longus muscles (EDL).…”
Section: Resultsmentioning
confidence: 94%